"A Colony of Alien Capital": French Investments, Polish Identity, and a Story of Murder in 1930s Warsaw. Issue 1 (2022) - Łazor, Jerzy
Abstract : This article explores public reactions to a murder of a foreign managing director running a French-owned textile factory in interwar Poland. The 1932 killing provoked an intense discussion in the press, which sheds light on Polish identity and narrative strategies used by the elites to rationalize the consequences of Poland's peripheral economic status. The study is based on discourse analysis of over 200 press articles. I argue that commentators saw the killing as the result of French policies in the factory, and interpreted these in turn as the result of either the Polish government's negligence, influenced by Paris's diplomats, or of global capitalism. The most dramatic arguments framed French policies in Żyrardów as a form of colonialism or slavery. This framing was based on the journalists' perception of French actions as transgressions of two imagined hierarchies: a geo-racial division of the world, and the local hierarchy of labor.